Translation Work by Pavle Solarić and Jovan Došenović - Савковић, Нада (Poznańskie Studia Slawistyczne, 2018)
During the times of Dositej Obradović (1739–1811), i.e. the period of Enlightenment in Serbia, advanced ideas were best spread through literature and the translation of contemporary authors was very common in Serbian literature. Obradović was the first to point out the importance of translation to the Serbs. He advocated the development of literature and culture modelled after more advanced cultures and based on the translation of useful works; he also believed that translation must adapt to the nature of target language. His views particularly influenced same writers from the region of Croatia, namely Pavle Solarić and Jovan Došenović, who were friends also. Solarić translated philosophical, geographical, historical and other documents, while Došenović, under the influence of others, compiled an arithmetic book, as well as the first collection of lyric poetry in recent Serbian literature, with the use of the imitatio procedure too. Translation influenced the genre, subject, style, and especially the linguistic development of Serbian literature.